Jeux Sans Frontieres: Tax Competition and Tax Coordination when Countries Differ in Size - Ravi Kanbur; Michael Keen (Queen's University, Department of Economics, 1991)
Closer international integration is putting increasing pressure on existing national tax structures. this paper uses a simple two-country model to address a range of policy concerns that consequently arise, focusing particularly on the role of national size. Differences in size exacerbate the inefficiency due to non-cooperative behavior, harming both countries. The smaller country would lose form harmonization to any tax rate between those of the non-cooperative equilibrium, but both countries would gain from the imposition of a minimum tax anywhere in that range. The fully optimal response to freer cross-border trade, however, may be to do absolutely nothing.
Keywords: 320; 423; 330